Existentialism as Portrayed in Stoner - Umi Nur Fadillah (POETIKA, 2022)
The purpose of this study is to analyze a novel titled Stoner (1965) written by an American academic and author, John Williams. Stoner follows the life of William Stoner, a professor of English Literature. Stoner comes from an impoverished farming family with a unique existential ethics. He works his way to become a university instructor and learns the magnitude of passion in the success of life. This study uses Lucien Goldmann’s Genetic Structuralist theory. The goals of this research are: 1) to analyze the structure of the literary work; 2) to understand the historical background that influences the novel; and 3) to reveal the author’s world view. The study shows that John Williams captures an existential tradition belonging to American lower-class famers who lived around the late 19th century. Stoner also captures the transformation of the existential tradition following a social, economic, and political transition. Camus’s The Myth of Sisyphus is used as a reference to explain the manifestation of the existential idea.